Kajian Pembangunan Smart Society Kota Bandung - Ega Ayu Gayatri; Ernady Syaodih (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Rancasari sub-district which is included in the Gedebage SWK with the theme of the technopolis area has a strong position in smart development because of the interest of this sub-district to accommodate the technopolis. Although the city of Bandung has implemented the smart city concept, there are still many problems with it, especially in the human resources component. The ability or skills and the total human resources in Bandung City are still lacking. In addition, the form of socialization carried out by the Bandung City Government regarding smart cities has not been evenly distributed in every district. The purpose of this study was to examine the development of a smart society in the Rancasari District. The approach method in this study is a mixed method using the Importance Performance Analysis method and qualitative descriptive analysis. The results of the analysis in this study indicate that the percentage of the average level of community satisfaction in the Rancasari District is 79,71% which indicates the level of conformity is not good so the community is not satisfied with the government's performance in the development of a smart society. The variables included in the low performance include the development of technology-based education management with Bandung Masagi character, the development of a collaborative and technology-supported security system, smart transportation, empowerment of social welfare potential, community social interaction, smart community, ICT-integrated community social assistance, improvement of social relations, smart education and security management systems by utilizing the Internet of Things (IoT). Abstrak. Kecamatan Rancasari yang termasuk ke dalam SWK Gedebage dengan tema kawasan teknopolis memiliki posisi yang kuat dalam pengembangan smart karena adanya kepentingan kecamatan ini untuk mewadahi teknopolis tersebut. Oleh karena itu, pemerintah memiliki program Bandung Smart City dalam dimensi smart society untuk mewujudkan ekosistem masyarakat yang humanis dan dinamis. Walaupun Kota Bandung sudah menerapkan konsep smart city, namun masih terdapat banyak permasalahan di dalamnya terutama dalam komponen SDM (Sumber Daya Manusia). Kemampuan atau keterampilan dan jumlah SDM di Kota Bandung yang masih kurang. Selain itu, bentuk sosialisasi yang dilakukan oleh Pemerintah Kota Bandung terkait smart city belum merata di setiap wilayah. Tujuan dari penelitian ini adalah untuk mengkaji pembangunan smart society di Kecamatan Rancasari. Metode pendekatan dalam penelitian ini yaitu mixed method dengan menggunakan metode Importance Performance Analysis dan analisis deskriptif kualitatif. Hasil analisis dalam penelitian ini menunjukkan bahwa persentase rata-rata tingkat kepuasan masyarakat di Kecamatan Rancasari sebesar 79,71% yang menunjukkan tingkat kesesuaian kurang baik sehingga masyarakat merasa belum puas terhadap kinerja pemerintah dalam pembangunan smart society. Adapun variabel yang termasuk ke dalam low performance meliputi pengembangan pengelolaan pendidikan yang berbasis teknologi berkarakter Bandung Masagi, pembangunan sistem keamanan yang kolaboratif dan didukung teknologi, smart transportation, pemberdayaan potensi kesejahteraan sosial, interaksi sosial masyarakat, smart community, bantuan sosial masyarakat yang terintegrasi TIK, peningkatan hubungan sosial masyarakat, smart education dan sistem manajemen keamanan dengan memanfaatkan Internet of Things (IoT).